Evaluation of UiTM student academic potential with correlation to motion technology / Norhanisa Kimpol - Kimpol, Norhanisa (2006)
This paper presents a research project on analyzing the effect of UiTM student academic potential with correlation to motion technology using Brain Optimization Synchronization System (BOSS™) table. It is an experimental method, or process, designed to relax the physical body and synchronize the electrical activity of the brain through horizontal rotation measurement. The brainwaves of twenty two samples were observed before and after the motion treatment using EEG equipment. In addition, each sample undergoes at least 5 sessions of treatments. A short interview was carried out for with each respondent to confirm the results. In general, the result shows that motion treatment produces significant improvement in terms of increasing alpha state signal of the brain. It was found that this treatment produced a significant improvement in terms of brain concentration improvements and focus in studies yielding 59% of samples improves their results, 9% of samples improve their sleeping quality and 5% of samples reduce their stress level.